PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (FINANCIAL STATEMENT FRAUD) MENGGUNAKAN BENEISH RATIO INDEX PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2018 - Anis Nurul Hadi; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This research aims to review the percentage of manufacturing companies who listing on BEI  2016-2018 period are classified as manipulators, non-manipulators, and excluding manipulators and non-manipulators  uses seven index count known as Beneish Ratio Index.  The indexes are Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Assets Quality Index (AQI), Sales Growth Index (SGI), Leverage Index (LVGI), Depreciation Index (DEPI), and Total Accrual To Total Assets Index (TATA). The research population is the whole company listing on the Indonesia stock exchange (BEI) 2016-2018 periods. Data collection method using documentation. The sample use non probability purposive judgement sampling, which samples are 25 companies in the above criteria. Detection by beneish ratio index, the results of research on manufacturing companies which listed 2016-2017 periods could be classified as manipulators are 12 % with the number of 3 companies, 2017-2018 periods is manipulators of 4 % with number of 1 company. 2016-2017 periods which as non-manipulators are 76 % with the number of 19 companies, 2017-2018 periods classified as non-manipulators are 88 % with the number of 22 companies. 2016-2017 periods classified as gray company are 12 % with the number of 3 companies, 2017-2018 periods as gray company are 8 % with the number of 2 companies. The ratio of the most determining the manipulation in this research is SGI , LVGI , and TATA.Keywords: Financial Statement Fraud, Manipulators, Non Manipulator, Gray Company, Beneish Ratio Index.